(untitled) (Research, Society and Development, 2024)
Introduction: The process of gender transition, which has always existed throughout human history, is currently offered through the Sistema Único de Saúde (SUS) in Brazil to all citizens free of charge. This is due to the understanding that procedure is an essential public health measure for this segment of the population. Beyond surgical, hormonal, or outpatient procedures, it concerns the mental health and integrity of a portion of the Brazilian population. Objective: To quantify the number of procedures and outpatient services provided by the Sistema Único de Saúde (SUS), as well as their prevalence over the years—from when it began to be offered in 2008 until 2022—and to compare the results according to the macro-regions of the country. Methodology: This is a mixed ecological study conducted through consultation of data from the Outpatient Information System of the Departamento de Informática do Sistema Único de Saúde do Brasil (DATASUS). The studied population consisted of all procedures and outpatient services provided to transgender individuals according to temporality and macro-regions. Results: During the period from 2008 to 2022, 85,889 procedures involving the aforementioned population were observed in Brazil. The South and Southeast regions reported a higher number of outpatient services and procedures, in contrast to the North region, which did not present any data during the analyzed period. Conclusion: More scientific productions on this subject are necessary to increase the visibility and interest of health professionals in this topic.